Numerical simulation of unsteady hydrodynamic performance of CRP. (15th December 2022) - Hu, Jian; Li, Fugeng; Sun, Shili; Wang, Yingzhu; Yan, Qinghao
Abstract: Strong hydrodynamic interference between forward and aft contra-rotating propellers (CRP) can result in load fluctuations, local blade vibrations, and noise. This study adopts a Reynolds-averaged Navier–Stokes solver (RANS) and a shear stress transport (SST) k − ω turbulence model to investigate the unsteady hydrodynamic performance of CRPs during uniform flow. The influences of time step and grid scale on the numerical simulation are discussed first. The numerical results of the open-water hydrodynamic performances of the CRPs agree well with experimental data. The fluctuation patterns of the hydrodynamic loads (i.e., force and torque) and propulsion efficiency of CRPs having different advance coefficients induced by the mutual hydrodynamic interference between the forward and aft propeller are investigated. A series of probes that rotate with the propellers are set upon the surface of the blades to analyze the unsteady local pressures under the hydrodynamic interference between the forward and aft propellers. Highlights: The fluctuation patterns of hydrodynamic loads and propulsion efficiency of CRP-6 in open water with different advance coefficients are investigated.